Kekuasaan dan Spiritualisme dalam Kepemimpinan Bupati Tabanan EkaxWiryastuti Periode 2010-2019 - Kharisma, Sonia; Bandiyah, Bandiyah; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2019)
ABSTRACTx This study aims to find out how spiritualism and power in the leadership of Tabanan Regent Eka Wiryastuti in the period of 2010-2019. Thisresearch is framed by the theory of Habitus by PierreBoudieau. The research method used in this research is qualitativedescriptive research with primary and secondary data usage, because it describes and illustrates phenomena that exist, both natural and human engineering, which paymore attention to the characteristics, quality, interrelationships between activities in relation to spiritualism and power in the leadership of the TabananRegent EkaWiryastuti in the period of 2010-2019. The resultsof this study are: first, Spiritualism and power form a correlations to generate strategic support for Eka Wiryastuti due to the accumulation of appropriate asset in Tabanan as the realm of strategy. Second the habitus of EkaWiryastuti can be explained through the meaning ofxdoxa, heterodoxa, andxorthodoxa in the battle ofdiscourse. Keywords : Eka Wiryastuti, Power, Spiritualism, The Habitus